2018
DOI: 10.1177/1553350618771410
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Vacuum-Assisted Closure for the Treatment of Anastomotic Leak Following Low Anterior Resection for Rectal Cancer, Is It Worthy?

Abstract: VAC therapy is an alternative to surgery that can be safely administered in an ambulatory setting. Early administration in the 6 weeks following surgery is an independent predictive factor for successful closure; however, colonic transit was only recovered in a small percentage of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…A total of 114 publications were found. Thirty of them, published between 2006 and 2018, were considered relevant . Four were excluded because they reported overlapping cases and only the most recent series were included .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 114 publications were found. Thirty of them, published between 2006 and 2018, were considered relevant . Four were excluded because they reported overlapping cases and only the most recent series were included .…”
Section: Resultsmentioning
confidence: 99%
“…Shortened healing time (median: 51 days) is proposed in the VAC group vs control group . According to different studies, the overall success rate of VAC therapy ranges from 79% to 94%, while the median heal time ranges from 20 to 244 days . Additional therapy with fibrin glue was applied to 13 out of 15 patients in Glitsch et al’s study .…”
Section: Discussionmentioning
confidence: 99%
“…Additional therapy with fibrin glue was applied to 13 out of 15 patients in Glitsch et al’s study . Three studies separated their participants into two groups according to the onset of treatment; the group of early term therapy had a better healing rate compared to the late term group . Strangio et al reported the data of the seven larger studies for VAC therapy of AL, which resulted in 94.3% healing rate of presacral abscess cavities …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations